In Situ Evaluation of Tensile Properties of Heat-Affected Zones From Welded Steel Pipes - Castelluccio, G. M.; Yawny, Alejandro Andres; Perez Ipiña, Juan Elias; Ernst, H. A. (Wiley Blackwell Publishing, Inc, 2012)
Fil: Castelluccio, G. M.. Georgia Institute of Technology; Estados Unidos